The Earlier, the Worse? Age of Onset of Sexual Interest in Children. (2nd July 2015) - Tozdan, Safiye; Briken, Peer
Abstract Aim Investigating the variability of the age of onset (AOO) of sexual interest in children (SIC) and the interrelations of important measures in individuals having a SIC, especially the role of the AOO. Methods A sample of 75 individuals from different contexts having a SIC was examined within an online survey. We explored the relations between AOO and other characteristics of the sample using correlation coefficients. The main outcome measures were self‐reported AOO of the SIC, its exclusiveness, its flexibility over time, participants' motivation to change it, and their self‐efficacy for modifying it. Results Results displayed that the AOO ranges from 6 to 44, and has a mean value of 17 and a median of 15 years. AOO correlates only with the flexibility, indicating that the earlier participants recognized their SIC, the less change they have experienced over time. Conclusion AOO of SIC may be broadly distributed and related to its flexibility. Further studies should clarify the relevance of these preliminary results and their possible implications for clinical practice. TozdanSandBrikenP. The earlier, the worse? Age of onset of sexual interest in children.J SexMed 2015;12:1602–1608.